1980
DOI: 10.2136/sssaj1980.03615995004400050048x
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic System for Precise, Rapid Analysis of Nitrous Oxide

Abstract: A gas chromatographic (GC) system for the sensitive, rapid, and precise analysis of nitrous oxide (N2O) was developed. The system employs a two‐part GC column that can be separated and the first section back‐flushed to remove contaminants while sample analysis continues. Nitrous oxide was detected by an electron capture detector. The GC system was suitable for analyzing small volumes of gas samples for ambient levels of N2O at the rate of 10 samples per hour with a precision of about 1 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(71 citation statements)
references
References 0 publications
0
70
0
Order By: Relevance
“…Analysis of N 2 O was conducted by procedures described by Mosier and Mack (1980). Gas samples were introduced into a 5.0 cm 3 sample loop and brought to ambient pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of N 2 O was conducted by procedures described by Mosier and Mack (1980). Gas samples were introduced into a 5.0 cm 3 sample loop and brought to ambient pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of N 2 O was determined using a 5870 series-II Hewlett-Packard gas chromatograph equipped with a Tracor electron capture linearizer (column type -capillary glass column; length -72 mm; oven temperature -70°C; detector temperature -400°C) which operated a Tracor 63 Ni electron-capture detector (Hewlett-Packard Company, Route 41, P.O. Box 900, Avondale, PA 19311-09900, USA) in the constant current pulsed mode (Mosier and Mack 1980). Incubation jars were opened, soil cores weighed, and bulk density and moisture content determined, only in 1991.…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary study indicated that the increases in gas concentrations within the chamber headspace were generally linear over a sampling period of up to 4 hours. Therefore, the fluxes were calculated (Mosier & Mack, 1980) using linear regression and the ideal gas law from equation (1):…”
Section: Gas Sampling and Measurementsmentioning
confidence: 99%